Impacts of Air Pollution and Heat Exposure on Reproductive, Maternal, Neonatal, Child, and Adolescent Health Outcomes in Nepal: A Scoping Review - Ramesh Sharma Poudel; Mandira Lamichhane Dhimal; Paribesh Bidari; Kristina Parajuli; Nisam Sharma; Prakash Dhimal; Pratik Subedi; Bibek Lamichhane; Spencer James Crocker; Allison Judkins; Bernhard Fassl; Meghnath Dhimal (Journal of Nepal Medical Association, 2026)
Introduction: Air pollution and heat exposure are major threats to reproductive, maternal, neonatal, child, and adolescent health; however, evidence from Nepal remains fragmented. Therefore, the objective of this review is to synthesises available evidence on the impact of air pollution and heat exposure on health outcomes in Nepal. Methods: A scoping review was conducted following Arksey and O'Malley's framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-extension scoping reviews. PubMed, Embase, Scopus, Web of Science, Google Scholar, and grey literature were searched from inception to September 2025. Results: Of 1,920 records, 27 studies were included (15 air pollution, 10 heat exposure, and 2 both). Household air pollution was associated with respiratory infections, pneumonia, and mortality, while ambient air pollution with respiratory infections and reduced fecundity. Higher temperatures were associated with diarrhoeal disease and adverse pregnancy outcomes, and lower temperatures with rotavirus infection and neonatal hypothermia, but nutritional outcomes were limited. Conclusions: Air pollution and temperature exposure are important determinants of reproductive, maternal, neonatal, child, and adolescent health outcomes in Nepal. Integrating climate risks into these health programmes and strengthening climate-sensitive disease surveillance are essential for evidence-based policy and practice.